Chemical structure and inhalation toxicity of lipopolysaccharides from bacteria on cotton. - Helander, I (1980)
Lipopolysaccharides from different bacteria isolated from cotton were purified and chemically analyzed. Their pulmonary toxicity to animals was tested in inhalation tests. Lipopolysaccharides from Agrobacterium and Xanthomonas were shown to differ from the others in that they contained no heptose and no non-hydroxylated fatty acids with a chain length of 12, 14, or 16 carbon atoms. Lipopolysaccharides from Pseudomonas putida, Enterobacter agglomerans, and Klebsiella oxytoca were found to cause an influx of polymorphonuclear leukocytes into the airways. Lipopolysaccharides from Agrobacterium sp. and Xanthomonas sinensis caused no significant invasion. The data point to substances in both the lipid A part and the core part of the lipopolysaccharides being responsible for the capacity to induce leukocyte invasion into the airways.